2015
DOI: 10.7314/apjcp.2015.16.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Is there any Potential Clinical Impact of Serum Phosphorus and Magnesium in Patients with Lung Cancer at First Diagnosis? A Multi-institutional Study

Abstract: Background: The aim of the study was to determine whether the expression of baseline phosphorus (P) and magnesium (Mg) levels were prognostic in terms of stage and overall survival (OS) in newly diagnosed non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) patients. Materials and Methods: Retrospectively, 130 patients were selected at the time of diagnosis oflung cancer (100 with NSCLC and 30 with SCLC), before the initialization of any chemo-radiotherapy. The median age was 67 (range 29-92). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…The selective uptake of phosphorus 32 P by tumors upon intravenous injection of radioactive phosphate has been known since the 1940 report by Marshak et al 30. supported by further observations313233. Recently, Papaloucas et al 34.…”
Section: Discussionmentioning
confidence: 88%
“…The selective uptake of phosphorus 32 P by tumors upon intravenous injection of radioactive phosphate has been known since the 1940 report by Marshak et al 30. supported by further observations313233. Recently, Papaloucas et al 34.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, phosphate is vital to normal physiological function and plays a role in intracellular signaling membrane function, energy metabolism, and bone mineralization (Sommer et al, 2007). A recent study reported that phosphorus and magnesium levels are predictive of disease in lung cancer patients, suggesting that phosphorus and magnesium levels may be important for stratifying patients to specific treatment protocols or intensifying their therapies (Kouloulias et al, 2015). Cancer cells that proliferate rapidly require a high amount of ribosome and other P-rich RNA components that are necessary to manufacture proteins (Kouloulias et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that phosphorus and magnesium levels are predictive of disease in lung cancer patients, suggesting that phosphorus and magnesium levels may be important for stratifying patients to specific treatment protocols or intensifying their therapies (Kouloulias et al, 2015). Cancer cells that proliferate rapidly require a high amount of ribosome and other P-rich RNA components that are necessary to manufacture proteins (Kouloulias et al, 2015). Consequently it is a theoretical belief that tumor cells are richer in phosphorus than the surrounding tissue, and that they are promoting their metastasis due to their nutrient demands (De Carvalho and Caramujo, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of nucleotides, membrane phospholipids, and phosphorylation intermediates in cell signaling require the participation of inorganic P. Rapidly proliferating cells, such as tumor cells, also need large amounts of P-rich ribosomes and RNA to synthesize proteins ( 25 , 26 ). Therefore, it is theoretically believed that an increase in serum P indicates that tumor cells are rapidly dividing and proliferating, which is why patients with a high P concentration have a poor response to NAC treatment.…”
Section: Discussionmentioning
confidence: 99%